DETERMINAN YANG MEMPENGARUHI AKUNTABILITAS KINERJA PEMERINTAH KOTA SEMARANG - Ririh Dian Pratiwi; Lilis Setyowati (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2019)
This study aims to observe several factors that contributed the local government accountability of local government performance the samples were selected by using a purposive sampling method. Involving all the staff of government employees on the financial section at the local government organization around units of Semarang City local government with the total number of 59 respondents. Source of data in this study are primary data. It was the data were collected by using sets of questionnaire measured by using likert scale. The data were analyzed by using multiple linear regression supported by SPSS version 20 software. The results of the study indicated that: (1) there was a not positive and significant effect application of public sector accounting on the accountability of local government performance, (2) there was a positive and significant effect of financial management on the accountability of local government performance, and (3) there was a positive and significant effect control of financial statement quality on the accountability of local government performance Keywords: Application of public sector accounting, financial management, control of financial statement quality, and accountability of local government performance.